Prototype Sistem Deteksi Serangan Pada Server Samsat Menggunakan Intrusion Detection System (IDS) Berbasis Snort - Meli Pitriyanti; Nelly Khairani Daulay; Satrianansyah; M. Agus Syamsul Arifin (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Problems from study This is Not yet exists system security server samsat to attack syn-flooding, so that is required Asystem Which can detect attack syn-flooding. On Method study use method survey and observation Where information collected from respondents through interview direct with manager office and manager server samsat. Results study This show that system based Snort Which designed for detect attack syn-flooding so thatcan detect attack syn-flooding the. From here can concluded that system This can Work with Good as steps early protection server for detect attack his flood on server Samsat